Use Of Innovative Technologies In Primary Class Lessons - Bobomurodov Kupaysin Abduvayitovich (Genius Publishing Group, 2024)
In this article, the application of innovative technologies and information technologies in the educational process will be highlighted in the educational process in terms of urgent tasks. Therefore, modern teaching methods, innovative and information the role and importance of technologies is extremely large.
Keywords: Innovative; pedagogical technology; technological